Gut Microbiota and Energy Homeostasis in Fish - Butt, Robyn Lisa; Volkoff, Helene (Frontiers in Endocrinology, 2019)
The microorganisms within the intestinal tract (termed microbiota) have been shown to interact with the gut-brain axis, a bidirectional communication system between the gut and the brain mediated by hormonal, immune and neural signals. Through these interactions, the microbiota might affect behaviors, including feeding behavior, digestive/absorptive processes (e.g. by modulating intestinal motility and the intestinal barrier), metabolism, as well as the immune response, with repercussions on the energy homeostasis and health of the host. To date, research in this field has mostly focused on mammals. Studies on non-mammalian models such as fish may provide novel insights into the specific mechanisms involved in the microbiota-brain-gut axis. This review describes our current knowledge on the possible effects of microbiota on feeding, digestive processes, growth and energy homeostasis in fish, with emphasis on the influence of brain and gut hormones, environmental factors and inter-specific differences.